2015
DOI: 10.1590/0104-07072015001572014
|View full text |Cite
|
Sign up to set email alerts
|

Family health strategy: a technological innovation in health

Abstract: The importance of the Family Health Strategy in the health sector in Brazil, and the debate on technology and technological innovation have led to the development of a theoretical reflection aiming to characterize the Family Health Strategy as a non-material technological innovation of the health field. In order to construct the text, the philosophical and sociological approach was used, as was the conceptualization of technological innovation, found in international documents and in Brazilian legislation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0
30

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 6 publications
1
18
0
30
Order By: Relevance
“…It should be highlighted that the FHS consists of a powerful space for the consolidation of PHE by performing shared practices in teams using different technologies to care for users, for having an inductive role in the interdisciplinary work of the team, in building a bond between team and users and the reformulation of traditional knowledge and practice in health 13 . In addition, the PHE is directed to the daily updating of the practices according to the theoretical, methodological, scientific and technological contributions available, as well as the joint construction of organizational, inter-institutional and/or intersectoral practices, directed at the policies in which health acts are inscribed 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be highlighted that the FHS consists of a powerful space for the consolidation of PHE by performing shared practices in teams using different technologies to care for users, for having an inductive role in the interdisciplinary work of the team, in building a bond between team and users and the reformulation of traditional knowledge and practice in health 13 . In addition, the PHE is directed to the daily updating of the practices according to the theoretical, methodological, scientific and technological contributions available, as well as the joint construction of organizational, inter-institutional and/or intersectoral practices, directed at the policies in which health acts are inscribed 14 .…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, as a result of the technological incorporation in the work environments, the health professionals are increasingly relating with nonhumans. 7 The impact of this process in the role of nursing and the efficacy of these technology in patient care has been one of the foci in nursing research throughout the past two decades. Nevertheless, considerable gaps remain in the general understanding of how nurses interact with technology.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Nevertheless, authors suggest caution in considering that, even with the established reduction of ICSAP, it is possible to find other determining factors besides the increase of primary care coverage and the ESF. [23][24] In fact, our study found a relationship between the ESF coverage and the increase in the number of registered hypertensive patients and the monitored ones in Mato Grosso do Sul, with no significant results regarding the reduction of harm and mortality due to hypertension in the State, 4 since the proportion of people with monitored hypertension when compared to the number of estimated in all groupings still does not reach the majority of patients (<50%).…”
mentioning
confidence: 99%